2019
DOI: 10.1093/jmcb/mjz103
|View full text |Cite
|
Sign up to set email alerts
|

Maternal miR-202-5p is required for zebrafish primordial germ cell migration by protecting small GTPase Cdc42

Abstract: Abstract In many lower animals, germ cell formation, migration, and maintenance depend on maternally provided determinants in germ plasm. In zebrafish, these processes have been extensively studied in terms of RNA-binding proteins and other coding genes. The role of small non-coding RNAs in the regulation of primordial germ cell (PGC) development remains largely unknown and poorly investigated, even though growing interests for the importance of miRNAs involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Many studies have demonstrated that miR-202-5p is an evolutionarily conserved miRNA associating with gonad development in vertebrates [22,27,28]. Recently, we reported that miR-202-5p regulated primordial germ cell migration by directly targeting Cdc42se1 [17]. In this study, we investigated a novel role of miR-202-5p in the immune response to RGNNV infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have demonstrated that miR-202-5p is an evolutionarily conserved miRNA associating with gonad development in vertebrates [22,27,28]. Recently, we reported that miR-202-5p regulated primordial germ cell migration by directly targeting Cdc42se1 [17]. In this study, we investigated a novel role of miR-202-5p in the immune response to RGNNV infection.…”
Section: Discussionmentioning
confidence: 95%
“…Zebrafish wild type AB line was purchased from the China zebrafish resource center. MiR-202-5p -/zebrafish were generated in our laboratory previously [17]. Fish were raised at 28 • C with 10 h darkness and 14 h light and were fed with commercial pellets twice a day.…”
Section: Fish Strains Cell Lines and Reagentsmentioning
confidence: 99%
“…Interestingly, hsa-miR-6511a-5p and hsa-miR-1910-3p all closely interacted with CDC42SE1. Jin and colleagues pointed out that CDC42SE1 not only targeted CDC42, but also suppressed CDC42 expression, and that the miR-202-5p/CDC42SE1 axis could regulate primordial germ cell migration by protecting CDC42 expression of CDC42 (Jin et al, 2019). Additionally, hsa-miR-144-3p was linked with three genes (ROCK1, CDC42EP3 and ARHGAP26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cdc42 and RhoL are known to control normal transfer of cytoplasm from nurse cells to oocyte in Drosophila [61] and Cdc42 knockdown in C elegans induces disruption of gonad primordium as well as absence of primordial germ cells [62]. As highlighted for Rac1, zebrafish Cdc42 can also impact the behavior of the highly migratory germ cells through its ability to control Blebs' expansion in migrating germ cells in vivo [63]. This is also relevant for other cell types such as mesendodermal cells [64], however, this is not the case in NC cells, since Syndecan 4 signaling pathway relies on Rac1 activity but not Cdc42 [18].…”
Section: Cdc42 In Cell Movement and Rearrangementmentioning
confidence: 99%